Effect of Mindfulness Meditation on Anxiety in Preoperative Patients Undergoing General Anesthesia: A Study at RSUD Wates - Luqyani, Hana Putri; Azizah, Aisyah Nur; Riyadi, Raden Sugeng (Adult Health Nursing Journal, 2025)
Introduction: Surgical procedures often cause patients to experience anxiety. Anxiety is a feeling of unease, worry, tension, and fear triggered by situations perceived as threats, the actual source of which is unknown. Preoperative anxiety can affect surgical outcomes. The application of mindfulness meditation during the preoperative phase is used to reduce anxiety levels and provide a calming effect. Objectives:  This study aims to determine the effect of mindfulness meditation techniques on pre-operative anxiety in patients with general anesthesia at RSUD (Regional General Hospital) Wates. Methods:  This type of research employed quantitative study using a quasi-experimental research design with a non-equivalent control group. The number of samples was 34 respondents and was divided into an experimental group and a control group. Data collection techniques applied the Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire. Data analysis performed using the Wilcoxon Signed Rank Test and the Mann-Whitney test. Results:  The results of this study indicate that there is a significant influence of the mindfulness meditation technique on the anxiety of pre-operative patients with general anesthesia of 0.000 <0.05, so Ha is accepted and H0 is rejected; this means that there is a significant influence on the level of anxiety of pre-operative patients. Conclusions:   The mindfulness meditation technique in this study was effective in reducing anxiety levels in pre-operative patients with general anesthesia.